Presentación: Puno Nuesta Tierra - Iguiñiz Echevarría, Javier (1999)
This issue of Allpanchis is dedicated to Puno and the most immediate reason for it is the celebration of the centenary of the birth of Puno intellectual Dr. Emilio Romero Padilla. In his tribute we have requested collaborations that present us with the current reality of the land and of education in Puno, as well as proposals for its development. In this presentation we are going to organize the summary based on the conclusions that seem most outstanding to us, making connections with Romero's work as we go along. Along with these contributions, we also have two approaches, one general and the other specific, on the work of the Catholic Church in the department.